KONSTRUKSI REALITAS DAN MEDIA MASSA (ANALISIS FRAMING PEMBERITAAN LGBT DI REPUBLIKA DAN BBC NEWS MODEL ROBERT N. ENTMAN) - Ardhina Pratiwi (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2018)
The development of mass media and the advancement of information technology have an important role in the success of the establishment of political goals. Consequently as a means of delivering the news, the mass media becomes the strongest channel in influencing and convincing people in shaping public opinion. The purpose of this study, the researcher wants to know more about how Republika media in framing issues of LGBT. Research method in this research uses qualitative with descriptive approach, in which the researcher explores the picture and social phenomenon contained of LGBT news. Data analysis in this research used Robert N. Entman model. The subject of this research is the online newspaper of Republika and BBC News, while the object of research is related the news of LGBT. Data collection techniques in this study using documentation and Purposive Sampling. The results of this study show that although Republika and BBC News are both preaching LGBT but the content of news is very different. Republika always prioritizes the Islamic religious ideology in framing LGBT related with the religious issues, while BBC News neutrally lays on LGBT with neither party nor LGBT actor in religious. But the equations of Republika and BBC News are both trying to package the content of the news in subtle and wise language to maintain their professionalism as a future medium that prioritizes universal, intelligent and professional values